COMPOSITION, AGE, AND SM-ND SYSTEMATICS OF ARCHEAN HIGH-MG GRANITOIDS (SANUKITOIDS) OF THE PANOZERO PLUTON, KARELIA - Chekulaev V.P.; Levchenkov O.A.; Arestova N.A.; Kovalenko A.V.; Guseva N.S.; Komarov A.N.; Ivanikov V.V. (My University, 2003)
A geochemical, geochronological, and isotopic study of rocks from the Panozero pluton in central Karelia was carried out. It was shown that the rocks make up a common subalkaline plutonic series and vary in composition from ultrabasic to acid varieties (42-67 wt % SiO 2). All rocks are markedly enriched in LILE (Ba, Sr, K, Rb) and LREE, at the same time remaining high in Mg (mg# is 0.62-0.45) and enriched in Cr and Ni. This geochemical signature is typical of Archean high-Mg diorites and granodiorites (sanukitoids) from other Precambrian shields but is described for the first time in the Baltic Shield. The U-Pb zircon age was estimated at 2727 ± 4.1 Ma for monzonite and 2737 ± 10 Ma for syenite. Taking into account the analytical uncertainty, both rocks are regarded as products of coeval crystallization. The zircon of a biotite lamprophyre dike that cuts the pluton is 2784 ± 4 Ma, i.e., much older than that of the plutonic rocks; thus, a xenogenic origin of the zircon can be suggested. The Nd isotopic composition shows that the depleted mantle was the source of rocks from the Panozero pluton. Positive εNd(t) values indicate the absence of long-term crustal residence time. The high contents of some LILE and LREE can be attributed to the influence of crustal fluids upon the source.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей